2012
DOI: 10.1016/j.jaci.2012.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analyses of atopic dermatitis and psoriasis reveal shared neutrophilic inflammation

Abstract: Background Atopic dermatitis and psoriasis are common inflammatory diseases, canonically described as involving distinct T-helper polarization and granulocytic infiltration. Acute atopic dermatitis lesions are associated with TH2 and eosinophilic inflammation, while psoriasis lesions are associated with TH1/17 and neutrophilic inflammation. Despite intensive investigation, these pathways remain incompletely understood in vivo in human subjects. Objective Using atopic dermatitis and psoriasis lesional skin as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 53 publications
7
81
1
1
Order By: Relevance
“…Th17 cells are proinflammatory via stimulation of keratinocytes to produce cytokines, chemokines, and vascular endothelial growth factor. Moreover, we have previously shown that increased numbers of Th17 cells are detectable in AD patients and that IL-17 promotes IgE production in vitro [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are proinflammatory via stimulation of keratinocytes to produce cytokines, chemokines, and vascular endothelial growth factor. Moreover, we have previously shown that increased numbers of Th17 cells are detectable in AD patients and that IL-17 promotes IgE production in vitro [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…112 Recently, a comparative transcriptomic analysis of AD and psoriasis revealed evidence for increased IL17 gene expression and shared neutrophilic inflammation in patients with these 2 skin diseases. 113 However, future studies are needed to determine whether IL-17 expression in the T H 2/T H 22 cytokine environment of AD would lead to different biologic responses than seen in the polarized T H 1/IL-17 environment of psoriasis.…”
Section: Immunologic Responsesmentioning
confidence: 99%
“…The best biomarkers for AD currently define patients who are Th2 polarized vs those who are not. In the future a combination of epidermal proteomics, genomics, gene transcriptomes, blood biomarkers in combination with the clinical phenotype will offer more precision in defining endotypes of AD (118)(119)(120). Approximately 80% of AD patients have elevated serum IgE levels, often with increased eosinophilia and serum levels of the Th2 chemokine thymus and activation regulated chemokine (TARC).…”
Section: Defining Endotypes In Atopic Dermatitismentioning
confidence: 99%